Large Shareholders as Monitors: Is There a Trade-Off between Liquidity and Control? - Maug, Ernst (Journal of Finance, 1998)
This paper analyzes the incentives of large shareholders to monitor public corporations. We investigate the hypothesis that a liquid stock market reduces large shareholders' incentives to monitor because it allows them to sell their stocks more easily. Even though this is true, a liquid market also makes it less costly to hold larger stakes and easier to purchase additional shares. We show that this fact is important if monitoring is costly: market liquidity mitigates the problem that small shareholders free ride on the effort of the large shareholder. We find that liquid stock markets are beneficial because they make corporate governance more effective.